Desipramine and fluoxetine antagonized 5,7-dihydroxytryptamine-induced lesion on rat hippocampal and cortical neurons. - Zhang Feng-qin; Luo Zhi-pu; Gong Zheng-hua (Acta Pharmacologica Sinica, 2016)
AIM: To assess the protective effect of desipramine (Des) and fluoxetine (Flu) on the neurons against the lesion induced by a selective serotonergic neurotoxin in vitro. METHODS: The 10-day cultured primary neurons of hippocampus and cortex of rat was exposed to 5,7-dihydroxytryptamine (5,7-DHT) to determine the optimal lesion concentration and duration. Before exposing to 5,7-DHT, Des and Flu was added to the medium for 30 min to observe the protective effects. RESULTS: The optimal concentration and duration for 5,7-DHT was 600 micromol.L-1 and 4 h, respectively. Both Des and Flu showed a protective effect in the dose range of 0.8 micromol.L-1 to 10 micromol.L-1 and 0.04 micromol.L-1 to 0.6 micromol.L-1, respectively, when the neurons were injured by 5,7-DHT 600 micromol.L-1 for 4 h. Flu showed a higher efficacy than Des. Both exhibited a more powerful protective effect on the hippocampal neuron than on the cortical neuron. CONCLUSION: The antidepressant effect of Des and Flu was attributed to their protective effect on the injured serotonergic neuron of the hippocampus and the cortex.